Magnetoelectroluminescence in organic light-emitting diodes - Lawrence, J; Lewis, A; Manolopoulos, D; Hore, P (AIP Publishing, 2016)
The magnetoelectroluminescence of conjugated organic polymer films is widely accepted to arise from a polaron pair mechanism, but their magnetoconductance is less well understood. Here we derive a new relationship between the experimentally measurable magnetoelectroluminescence and magnetoconductance and the theoretically calculable singlet yield of the polaron pair recombination reaction. This relationship is expected to be valid regardless of the mechanism of the magnetoconductance, provided the mobilities of the free polarons are independent of the applied magnetic field (i.e., provided one discounts the possibility of spin-dependent transport). We also discuss the semiclassical calculation of the singlet yield of the polaron pair recombination reaction for materials such as poly(2,5-dioctyloxy-paraphenylene vinylene) (DOO-PPV), the hyperfine fields in the polarons of which can be extracted from light-induced electron spin resonance measurements. The resulting theory is shown to give good agreement with experimental data for both normal (H-) and deuterated (D-) DOO-PPV over a wide range of magnetic field strengths once singlet-triplet dephasing is taken into account. Without this effect, which has not been included in any previous simulation of magnetoelectroluminescence, it is not possible to reproduce the experimental data for both isotopologues in a consistent fashion. Our results also indicate that the magnetoconductance of DOO-PPV cannot be solely due to the effect of the magnetic field on the dissociation of polaron pairs.